Karakterisasi Tokoh Suhartini Dalam Monolog Pengakuan Seorang Wanita Pemalu Karya Iswadi Pratama - Tafsir Hudha (Institut Seni Indonesia Surakarta, 2021)
The script for the Confession of a Shy Woman, the adaptation of the Iswadi Pratama script, is a monologue script, which is a form of single play or individual role art (which is the actor’s singularity) the conflict in the play must be able to be fully described. Monologue is considered as one of the peaks of personal (individual) acting ability which is used as a starting point for the strength of collective acting or ensemble acting, which is a form of acting which is a means of describing conflicts in theater that rests on ‘dialogue’ and is no longer just ‘monologue’. In creating the characterization of Suhartini’s character, it must be based on deepening the script to find the character’s vision, impulse or encouragement of the character, the character’s motivation and the emotional depth of the character. This requires work to explore the problems faced by the characters, formulate character characterizations and the next work is to transform character characterizations into the characters themselves. Such tracing requires analytic work on the script to be played, especially characterization analysis, further processing of the action, requires precision in order to achieve maximum results. Suhartini’s character in the manuscript Confession of a Shy Woman, is a picture of an introverted woman who has strong principles in life, and upholds her self-esteem, but has shy, pendian and anti-social characteristics.